Tracing the Idea of the Social Function and Its Practice in Several Countries - Ananda Prima Yurista; Nurhasan Ismail (Yuridika, 2025)
The idea and regulation of the social function are contained in Law No. 5 of 1960 on Basic Regulations on Agrarian Principles (Basic Agrarian Law–BAL) in order to realize welfare for the people. The concept of the social function was developed by Leon Duguit. The concept of the social function is not an idea that has only developed in Indonesia; it has been applied in several countries, including Brazil, the United States, Colombia, Chile, and Mexico. Based on this, it is interesting to examine the development of the idea of social functions in several countries so that it can then be used as a lesson learned for the development of the idea of social functions by using legal research methods, in the form of normative juridical methods. One of the findings in this article is that the regulation of social functions over property in Brazil, Colombia Chile, and Mexico is regulated in the constitution, and then further regulated in the Civil Code, which is equivalent to a law. In contrast, when tracing the regulation of social functions in the United States, the term used is social obligation, and the regulation of social obligations is enshrined in jurisprudence. The method of approach used is normative juridical.